The Significant Connection between Communicative Competence and Cognitive Ability in Speaking English of English Debating Team - Hapsari, Prima Dona; Wirawan, F.A. Wisnu (Bina Nusantara University, 2018)
The purposes of the research were to find out whether the communicative competence in English speaking skills had a significant relationship with students' cognitive abilities was English speaking skill the most important achievement. How cognitive abilities and communicative competencies in English speaking skills were managed for the primary purposes of the English debating team. This research combined both qualitative and quantitative research. It used a descriptive method by distributing questionnaire, doing a survey, using observation, and doing an in-depth interview as the methods to collect data. The informants were twelve students who participated in the national teams of English Debating Championship of Institut Seni Indonesia Yogyakarta from 2013-2017. The results of this research reveal that there is a significant connection between communicative competence and cognitive ability in which cognitive ability has an important impact on thinking, critical analysis, and creativity. Furthermore, cognitive ability gives a direct influence on communicative competence in speaking English. This communicative competence is reflected in the ability to produce critical-intellectual andcommunicative-factual sentences in doing the analysis and giving the argumentation.